Optimization Of Abnormal High Pressure Heater (HPH) Operating Pattern to Reduce Heatrate Of Adipala Power Plant 1 X 660 MW - Ridwan, Muhammad; Ghulam, Ahmad Analial (Universitas Wiralodra, 2023)
PLTU Adipala has three HPH (High Pressure Heaters) that have a very essential role in its operations. In The current condition, these three HPH are in a series. Which is, if the middle HPH has a problem during the cycle experiences and must be out-serviced, then the after HPH also must be out-serviced. This situation can increase the heat rate value because two HPH are out of service. Therefore, an alternative mode of HPH operation is needed to press the increase of heatrate and also prevent a decrease in generator efficiency at the same time. Simulations were carried out to obtain the most optimal operating pattern. This simulation was carried out using the Cycle Tempo software. The heat balance cycle is made in the Cycle Tempo software for each condition and filled in with the parameters. Then it runs to obtain the simulation results. The first condition is a normal HPH operating has a heat rate of 2071.4 kcal/kwh. The second condition is a condition where HPH 7 and 8 are out of service and have a heat rate of 2161 kcal/kwh. The third condition is only HPH 7 that is out of service and HPH 8 is streamed to HPH 6 which has a heat rate of 2118 kcal/kwh. The fourth condition is only HPH 7 which is out of service and HPH 8 is streamed to the condenser, which has a heat rate of 2150 kcal/kwh.